Determinants of transparency and disclosure –evidence from post-transition economies - Arsov, Sasho; Bucevska, Vesna (Taylor and Francis, 2017)
In this paper, we examine the patterns of behaviour of companies from former socialist countries related to the application of good corporate governance practices. We try to assess the level of transparency and to determine if there are any factors that systematically influence corporate behaviour in this regard. Using a sample of 145 companies from Croatia, Macedonia, Slovenia and Serbia, we apply Standard & Poor’s (S&P) methodology for assessment of transparency and disclosure levels and find that the companies in these countries generally lag in terms of transparency behind their peers worldwide as measured one decade ago. Additionally, using the same sample, we apply a regression analysis and conclude that the level of transparency is positively related to the size of the company and the need for external financing, but negatively to the concentration of ownership and we also observe important country effects. We do not find a statistically significant relationship between transparency and profitability and relate this finding with the prevailing attitude of the companies towards the stock market. Having in mind the different scores by country and by area of disclosure, we believe that there is still scope for improvement using proper advising and public policy measures.
Keywords: Transparency; disclosure; corporate governance; stock market; transition